VARIATIONS IN FLEXIBILITY DURING THE MENSTRUAL CYCLE IN COLLEGE ATHLETES - Moiso Marín, Fiorella (2016)
With the purpose of considering the existence of variations in the flexibility in 2 phases of the menstrual cycle (menstrual phase and ovulatory phase) of college athletes, functional and multi-articular flexibility tests were applied to 28 women with an average age of 20.9 ± 3.0 years, a moderate level of stress, few hours of sleep related to high levels of stress, and a habit of alcohol consumption of at least once a month in the majority of them. In the general population, the t Student did not show significant differences in the 2 phases evaluated. The flexibility results were 50.73 ± 17.97º and 51.97 ± 16.76º (t = -1.031; p = 0.312) in the anteversion shoulder test, 58.14 ± 17.28º y 60.53 ± 17.12º (t = -1.754; p = 0.091) in the retroversion shoulder test, and 110.63 ± 7.56 cm y 110.48 ± 8.31 cm (t = 0.252; p = 0.803) in the Sit and Reach Test, in the ovulatory and menstrual phase, respectively. Nevertheless, the stratified t Student found more flexibility in the ovulatory phase in women who consumed alcohol regularly (p= 0.020) and had a higher level of stress (p= 0.040) in the anteversion shoulder test; in women who did not sleep adequately (p= 0.030), slept less than 7 hours daily (p= 0.040), or had a short luteal phase-less or equal to 9 days- (p= 0,006) in the retroversion shoulder test. In conclusion, there were no statistically significant variations in the flexibility during the menstrual cycle in the general population. However, certain socio-demographic and clinical conditions seem to predispose variations throughout it.